Effects of taichi on physical and psychological health of college students: A systematic review - Qi, Fengmeng; Soh, Kim Geok; Mohd Nasirudddin, Nasnoor Juzaily; Mai, Yiqiang (Frontiers in Physiology, 2022)
Background: Increasing studies have documented taichi’s usefulness in physical and psychological health in various participants, especially patients or the elderly. However, there is a need for a systematic review to evaluate its effects and health benefits among college students. Objective:The present study aims to evaluate the current literature surrounding the effects of taichi on physical and psychological health among college students and identify the experimental areas for future research to establish guidelines for learning and teaching taichi in university. Methods: The literature search involved several databases (PubMed, EBSCOhost, Web of Science, Scopus, and CNKI). Subsequent research utilised the Preferred Reporting Items for Systematic Reviews and PRISMA checklist. In addition, the "QualSyst" tool assessed the quality of full-text articles. Results: A total of 22 articles were analysed, out of which eight were strong, and 14 were of moderate quality. It is challenging to conduct a meta-analysis since the research contents were distributed differently. The general finding demonstrated that Taichi interventions have beneficial effects on college students. For example, the physical and psychological health benefits compared to other control groups include balance, leg strength, flexibility, cardiopulmonary functions, reducing stress, anxiety, and depression, and improving attention. However, there are some uncertain parameters in a state of poor or no evidence, such as upper strength, mood, and psychoticism. Conclusion: Overall, this study shows that Taichi exercise is beneficial for college students compared to the control group. Evidence of health benefits for females is more than males. In addition, the current evidence showed that the effectiveness of taichi does not match some other sports such as Pilates, Yoga, Mindfulness courses, and even bodybuilding exercise. This research analyzed the mind-body mechanism of included studies. It revealed that it is difficult for college students, as a beginner of Taichi, to regulate an even breathing and quiet mind while maintaining low posture movements. Therefore, this study assumes that relaxation theories and approaches of Taichi that are easier to understand and closer to Chinese traditional Taichi theory are more appropriate in the research trials compared with coordination theory.